Effects of an artificial oyster shell reef on macrobenthic communities in Rongcheng Bay, East China - 徐勤增 张立斌 张涛 周毅 夏苏东 刘辉 杨红生 (Chinese journal of oceanology and limnology, 2014)
An artificial oyster shell reef was deployed in Rongcheng Bay, East China. However, the effects of this reef on the surrounding macrobenthic communities were unknown. We compared sedimentary factors, macrobenthic biomass, abundance, and community composition and ecological indicators between the reef and non-reef areas over a one year period. The mean values for chlorophyll a （Chl a）, total organic matter （TOM）, total organic carbon （TOC）, and total nitrogen （TN） content in surface sediments in the reef area were slightly higher than those in the non-reef area. The Chl a levels differed significantly between the two areas, but the TOM, TOC, and TN were not significantly different. The abundance of crustaceans was significantly different between the two areas, but the abundance and biomass ofpolychaetes, echinoderms, mollusk did not differ significantly. The permutational multivariate analysis of variance （PERMANOVA） revealed that the macrobenthic community differed significantly through time and analysis of similarity multivariate analyses （ANOSIM） revealed that the macrobenthic community differed significantly in some months. The ecological indicators revealed that the environmental quality of the reef area was slightly better than that of the non-reef area. Overall, our results suggest that the artificial oyster shell reef may change the macrobenthic community and the quality of the environment. Despite the lack of an effect in the short term, long-term monitoring is still needed to evaluate the effects of artificial oyster shell reefs on macrobenthic communities.